Children’s Physical Health and Implementation of Post-Pandemic Healthy Behavior - Kuswanto, Cahniyo Wijaya; Pratiwi, Dona Dinda; Denata, Galuh Yuliar (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – The physical condition of children needs to be analyzed in the field, whether COVID-19 affects their health or not, and how to implement post-pandemic healthy living behaviours in the school and community environment so that children are truly safe when hanging out with their friends.Design/methods/approach – This research uses a case study qualitative method by collecting data using observation, interviews, and document analysis. Source triangulation is a means to assist in the validity of the data.Findings – The results showed that the children’s physical health began to improve. It is supported by the current improvement in children’s health, as well as free physical activity that can be carried out at school or in the community. In addition, a COVID vaccine helps the child’s immune system to be more robust against disease. The implementation of clean and healthy living behaviours in schools and the community is very supportive, as evidenced by hand-washing equipment in every corner of the house and school.Research implications/limitations – The limitations of this study are the narrow research subjects, so general conclusions cannot be drawn. However, the research results can be stakeholder input to invite the public to continue implementing health protocols.Practical implications – The results show field findings found a decline in the prokes provision of infrastructure for clean and healthy living behavior in schools and the community.Originality/value – This study proves that young children are far away from COVID-19. It is proven at home and school. Many children are in good health and fit and doing everyday activities.Paper type: Research paper